The neuroinvasive potential of SARS‐CoV2 may play a role in the respiratory failure of COVID‐19 patients - Li, Yan‐Chao; Bai, Wan‐Zhu; Hashikawa, Tsutomu (Journal of medical virology, 2020)
Following the severe acute respiratory syndrome coronavirus (SARS‐CoV) and Middle East respiratory syndrome coronavirus (MERS‐CoV), another highly pathogenic coronavirus named SARS‐CoV‐2 (previously known as 2019‐nCoV) emerged in December 2019 in Wuhan, China, and rapidly spreads around the world. This virus shares highly homological sequence with SARS‐CoV, and causes acute, highly lethal pneumonia coronavirus disease 2019 (COVID‐19) with clinical symptoms similar to those reported for SARS‐CoV and MERS‐CoV. The most characteristic symptom of patients with COVID‐19 is respiratory distress, and most of the patients admitted to the intensive care could not breathe spontaneously. Additionally, some patients with COVID‐19 also showed neurologic signs, such as headache, nausea, and vomiting. Increasing evidence shows that coronaviruses are not always confined to the respiratory tract and that they may also invade the central nervous system inducing neurological diseases. The infection of SARS‐CoV has been reported in the brains from both patients and experimental animals, where the brainstem was heavily infected. Furthermore, some coronaviruses have been demonstrated able to spread via a synapse‐connected route to the medullary cardiorespiratory center from the mechanoreceptors and chemoreceptors in the lung and lower respiratory airways. Considering the high similarity between SARS‐CoV and SARS‐CoV2, it remains to make clear whether the potential invasion of SARS‐CoV2 is partially responsible for the acute respiratory failure of patients with COVID‐19. Awareness of this may have a guiding significance for the prevention and treatment of the SARS‐CoV‐2‐induced respiratory failure. Research Highlights SARS‐CoV2 causes epidemic pneumonia characterized by acute respiratory distress. This novel coronavirus is similar to SARS‐CoV in sequence, pathogenesis, and cellular entry. Some coronaviruses can invade brainstem via a synapse‐connected route from the lung and airways. The potential invasion of SARS‐CoV2 may be one reason for the acute respiratory failure. Awareness of this will have guiding significance for the prevention and treatment.